Epoxy/unsaturated polyester blends via post-curing process for marine applications - Pakaya, Fahriadi; Nantan, Yurika; Tappy, Marinus S.; Simanjuntak, Raman GTH; Huwae, Jozua Ch.; Syam, M. Yusuf; Siregar, Izhary; Subawa, I Nyoman; Urun, Wilfred Yan Krol (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Epoxy resins and unsaturated polyester resins are widely used thermosetting polymers with applications in construction, electronics, and maritime industries. However, their respective limitations, such as brittleness in epoxy and reduced mechanical strength in unsaturated polyester, hinder their broader utilization. To address these challenges, blending the two polymers offers a promising approach to enhance their performance. This study investigates the mechanical and thermal properties of epoxy/unsaturated polyester blends enhanced through a post-curing process with stepwise temperature increases. The blends were characterized using FTIR, tensile, impact, and hardness tests in accordance with ASTM standards. Results demonstrate a synergy between the two polymers, with certain compositions (e.g., 90% epoxy/10% unsaturated polyester) achieving improved tensile strength, flexibility, and impact resistance. The highest tensile strength (54.45 N/mm²) was recorded in blends with > 50% unsaturated polyester, while optimal impact toughness (0.1438 J/mm²) was achieved with 90% epoxy and 10% unsaturated polyester. FTIR analysis revealed specific interactions between functional groups that contribute to the improved properties. These findings highlight the potential of epoxy/unsaturated polyester blends for demanding industrial applications, particularly in marine environments requiring high thermal stability and mechanical performance.